“Others Like Him”: The Alberta Pioneer in Popular Culture & Folk Poetry - Lyon, George (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1993)
In the popular culture of Alberta, the pioneers of the province’s historic era are commonly identified as cowboys. Pioneers are portrayed in a fashion that conforms closely to the pattern Bakhtin termed epic, that is, as static heroes whose grand deeds may serve as details but not as quotidian models. In Albertan folk poetry, however, “pioneers” means “homesteaders”, a group which lacks both the glamour and the epic status of the cowboy. This folk poetry cannot be said to speak in Bakhtin’s novel mode, but it nevertheless offers a multivoiced account of the legacy of the first European exploiters of the northern prairies.